Dodecylamine-Loaded Halloysite Nanocontainers for Active Anticorrosion Coatings - Falcón, Jesus Marino; Sawczen, Tiago; Aoki, Idalina Vieira (Frontiers in Materials, 2015)
Currently the most promising approach in the corrosion protection by smart coatings is the use of nanoreservoirs loaded with corrosion inhibitors. Nanocontainers are filled with anti-corrosive agents and embedded into a primer coating. Future prospective containers are halloysite nanotubes due to their low price, availability, durability, with high mechanical strength and biocompatibility. The aim of this work is to study the use of halloysite nanotubes as nanocontainers for encapsulated dodecylamine for active corrosion protection of carbon steel. Halloysite clay was characterized by XRD and TGA- thermogravimetric analysis techniques. Halloysite nanotubes were loaded with dodecylamine and embedded into an alkyd primer with a weight ratio of 10 wt.% . The anticorrosive performance of the alkyd primer doped with 10 wt.% of entrapped-dodecylamine halloysite was tested on coated carbon steel by direct exposure of the coated samples with a provoked defect into 0.01 mol/L NaCl corrosive media using electrochemical impedance spectroscopy (EIS) and scanning vibrating electrode technique (SVET). EIS and SVET measurements showed the self-healing properties of the doped alkyd coating. Coated samples were also evaluated in a salt spray chamber and the self-healing effect was unequivocally noticed.